PENGARUH PROFITABILITAS, LEVERAGE OPERASI DAN TINGKAT PERTUMBUHAN PERUSAHAAN TERHADAP STRUKTUR MODAL PADA INDUSTRI MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA. - Gultom, Metro; Silalahi, Donalson (UNIKA Santo Thomas, 2013)
The purpose of this study that analyze the influence of Profitability, Leverage Operations and Growth Rate on Industrial Manufacturing Company listed on the Indonesia Stock Exchange. The data used in this research is secondary data obtained from the Indonesia Stock Exchange. The method used in this study is multiple regression. From the results of the analysis indicate that the Profitability, Leverage Operations and Corporate Growth Rate simultaneously have a significant impact on capital structure, while partial profitability and significant negative effect on the Capital Structure, while Operating Leverage and no significant positive effect on capital structure, while the Company Growth positive and significant effect on the Capital Structure in Manufacturing Industry listed in Indonesia Stock Exchange. Variable Profitability, Leverage Operations and Corporate Growth rate can explain the variation in capital structure policy in Manufacturing Industry in Indonesia Stock Exchange amounted to 75.6 percent.